Analysis of the effective propellants of tourism development in Rasht metropolis based on future studies approach - Farhad Javan; Sirous Hojjat; Mohammad Seyfizadeh (پژوهش‌های برنامه و توسعه, 2021)
linking of futures studies with the tourism industry can create a suitable position for research in the field of urban tourism. The present study is seeking to analyze of key affecting propellants on the development of tourism in Rasht city with future studies approach. The present study in terms of purpose is qualitative and in terms of data collection method and final results is applied. To conduct this research, 34 factors were extracted as the main factors in 5 dimensions (environmental, socio-cultural, planning-institutional, infrastructure-welfare, economic) and Then the propellants factors were identified by using the Delphi method. For data analysis, the interaction analysis method was used in MICMAC software. The results of the study indicate that due to the distribution of variables, tourism development in the Rasht metropolis is unstable. Then the key factors were ranked that the variables of development of relations with neighbors, animal life, the existence of shopping centers, were ranked first to third, respectively. According to the studies conducted in this field, so far no study has been conducted in relation of tourism development futures studies in the studied area. Finally, four scenarios were presented for the future studies of the tourism industry in the Rasht metropolis.